Middle Mesial Canal an Extra Entity: A Case Report - Sana Farooq (Highlights on Medicine and Medical Science Vol. 3, 2021)
The primary objective of endodontic therapy is to achieve a three-dimensional obturation of the root canal space to remove the tissue debris, microorganisms and their by products after a proper biomechanical preparation of the pulp chambers. The missing canal of complex root canal morphology is major reason for endodontic failure. The use of magnification, illumination, recent advancements, diagnostic aids and techniques help in minimizing the incidence of missing a canal. This case report describes the rare management of a left mandibular first permanent molar requiring root canal treatment with an additional Middle Mesial Canal (MMC) in the mesial root. Clinicians experience and approach is a key factor in negotiation and management of these aberrant canal configurations. After a proper access cavity preparation, clinicians should spend time in examining the mesial sub pulpal groove to detect and negotiate additional canal.